Leonurine promotes the maturation of healthy donors and multiple myeloma patients derived-dendritic cells via the regulation on arachidonic acid metabolism - Chen, Cheng; He, Lin; Wang, Xi; Xiao, Rong; Chen, Shu; Ye, Zichen; Wang, Xuemei; Wang, Yu; Zhu, Yizhun; Dai, Jingying (Frontiers in Pharmacology, 2023)
Objective Leonurine is a bioactive alkaloid compound extracted from Leonurus japonicus Houtt, which potentially has immunomodulatory effects. The immunomodulatory effect and mechanism of leonurine on monocyte derived dendritic cells (moDCs) from healthy donors (HDs) and multiple myeloma (MM) patients were investigated for the first time. Methods Peripheral blood from HDs and MM patients was isolated for peripheral blood mononuclear cells (PBMCs). The generation of moDCs was conducted by the incubation of monocytes from PBMCs in the medium consisting of RPMI 1640 medium, 2mmol/L L-glutamine, 5% human serum, 800U/mL GM-CSF, 500U/mL IL-4, 100U/mL penicillin and 0.1mg/mL streptomycin. During the incubation of 7 days, the cells were administrated with 1μM leonurine or 1×PBS as the control group. On the 8th day, cells were harvested. The expression of maturation associated surface markers CD40, CD83 and HLA-DR on moDCs was analyzed by flow cytometry. Moreover, moDCs with or without 1μM leonurine administration were evaluated by LC-MS/MS for metabolomics which was further analyzed for the potential mechanism of leonurine on moDCs. Results The proportion of moDCs in the harvested cells was significantly higher in the HD group (n=14) than in the MM patient group (n=11) (P=0.000). Leonurine significantly enhanced the median fluorescence intensity of CD83, HLA-DR and CD40 expression on HD-moDCs (n=14; P=0.042, P=0.013, P=0.084) as well as MM paitent-moDCs (n=11; P=0.020, P=0.006, P=0.025). The metabolomics data showed that in moDCs (HD, n=15), 18 metabolites in the pathway of arachidonic acid metabolism showed significant differences between the leonurine group and the control group (VIP all > 1 and P all <0.05). To be specific, 12-OxoETE, Prostacyclin, Lecithin, 15(S)-HETE, 15-Deoxy-Delta12,14-PGJ2, PGB2, PGE2, 6-Keto-PGE1, 8,9-DHET, 12-Keto-LTB4, 11(R)-HETE, 15-Keto-PGF2a, PGG2, PGA2, PGF2a, 20-COOH-LTB4 were significantly up-regulated in the leonurine group than in the control group, while TXB2 and Arachidonic Acid were significantly down-regulated in the leonurine group than in the control group. Conclusions Leonurine significantly promotes the maturation of moDCs derived from HDs and MM patients, the mechanism of which is related to arachidonic acid metabolism.